Pancreatic Leiomyosarcoma With Schistosomiasis Hematobia: A Case Report and Literature Review - Li, Qiang; Staiculescu, Daniel; Zhou, Yurong; Chen, Jiang (Frontiers in Oncology, 2021)
Pancreatic 1eiomysarcoma (PL) is a very rare malignant pancreatic neoplasm, and the prognosis of PL is very poor. We are reporting a PL with schistosomiasis haematobia, which has not been reported yet. The patient had been followed up by imaging for three years. There is no specific imaging features by the first MRI. The second imaging examination demonstrated an enlarged heterogeneous tumor mass in the body-tail of pancreas. The patient underwent pancreatectomy, splenectomy and lymph node dissections. Sixteen months after the tumor resection, follow-up CT and MRI remonstrated the tumor metastasis in the liver and lung. PL has non-specific clinical manifestations and imaging characteristics, the early diagnosis is very challenging. When it is difficult to distinguish between benign and malignant pancreatic lesions, short-term imaging follow-up is preferred. In this case report, we discuss the relationship between PL and schistosomiasis haematobia other than diagnosis and differential diagnosis, with a review of the related literature.